Uterine Artery Pulsatility Index as a Pre-eclampsia Predictor in the 3 Trimesters in Women with Singleton Pregnancies - Guzmán, Yuly Natalia; Uriel, Montserrat; Ramírez, Alexandra Porras; Romero, Ximena Carolina (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2021)
Objective To evaluate the mean uterine artery pulsatility index (UtAPI) in each trimester of pregnancy as a predictor of early or late pre-eclampsia (PE) in Colombian pregnant women.Methods The UtAPI was measured in singleton pregnancies in each trimester. Uterine artery pulsatility index as predictor of PE was evaluated by odds ratio (OR), receiver operating characteristic (ROC) curves, and Kaplan-Meier diagram.Results Analysis in the 1st and 3rd trimester showed that abnormal UtAPI was associated with early PE (OR: 5.99: 95% confidence interval [CI]: 1.64–21.13; and OR: 10.32; 95%CI: 2.75–42.49, respectively). Sensitivity and specificity were 71.4 and 79.6%, respectively, for developing PE (area under the curve [AUC]: 0.922). The Kaplan-Meier curve showed that a UtAPI of 0.76 (95%CI: 0.58–1.0) in the 1st trimester was associated with early PE, and a UtAPI of 0.73 (95%CI: 0.55–0.97) in the 3rd trimester was associated with late PE.Conclusion Uterine arteries proved to be a useful predictor tool in the 1st and 3rd trimesters for early PE and in the 3rd trimester for late PE in a pregnant population with high prevalence of PE.
Keywords: uterine artery doppler; preeclampsia; pregnancy; perinatal care; screening